Association between food intake and mental health problems among preschoolers in China - Jin, Qiyun; Liang, Yi; Miao, Junjie; Xiong, Yi; Liu, Zhijun; Xue, Hongmei; Li, Zengning (Frontiers in Public Health, 2022)
Objective: Our knowledge of associations between specific types of food and mental health problems in preschool children, an important developmental period, remains scarce. Using a large sample size and a brief measure, we aimed to examine associations between food groups and mental health problems in preschoolers. Methods: A descriptive cross-sectional study was conducted among 19,548 preschoolers in nine counties in China using a two-stage cluster sampling method. Information on food frequencies, physical activity, sedentary behavior, and sleep conditions was collected by a parent-reported questionnaire. Mental health status was assessed by a parent-reported Strength and Difficulty Questionnaire (SDQ). Height and weight were measured, and BMI was calculated. Relationships between specific types of food groups and mental health status were examined using multivariable regression modeling. Results: Of the present study sample, 47.45% of children were girls. Boys had higher scores relating to total difficulties, conduct problems, hyperactivity, and peer problems than girls but lower scores in emotional symptoms and prosocial Behavior. Children with more types of food categories tended to get lower SDQ total scores even after adjusting for confounding variables (p<0.0001). The subscale scores of SDQ varied depending on the types and numbers of food consumed. Notably, boys’ mental health problems were more likely to be associated with their consumed food type. Processed meat frequency intake among boys and girls was negatively related to prosocial behavior and negatively associated with the SDQ total and the other subscale scores (p<0.05). Adequate intake frequency of confectionery (2-4 times/week) was beneficial to their emotions, conduct, and total difficulties and was also beneficial for peer and prosocial behavior for boys (p<0.05). Conclusion: Diverse food categories and adequate frequency of confectionery were found to be beneficial for children's mental health, with the exception of processed meat. These findings provide novel information and supportive data for children's dietary guidelines and the improvement of mental health.